2020
DOI: 10.22207/jpam.14.2.41
|View full text |Cite
|
Sign up to set email alerts
|

Application of Herbal Medicines for Obesity Treatment in the Polycystic Ovarian Syndrome Women

Abstract: Polycystic ovarian syndrome (PCOS) is a frequent disorder commonly found in reproductive-aged women. The disease PCOS in women is considered to be complex heterogeneity, which indicates the combined combination of genetics and environmental interaction factors. Insulin resistance, type 2 diabetes mellitus, and obesity are known to be the risk factors for the development of PCOS. The prevalence of obesity in Saudi Arabia is ripening equally in both men and women. Herbal Medicines are often used for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…There were no significant differences between the exercise group and the ginger supplementation group, except in the measured weight of women, where the exercise group showed better results [29]. Results of the study conducted by Alghamdi confirmed a previous finding, where women treated with ginger capsules had lower values of BMI, insulin, and high and low-density lipoproteins [30].…”
Section: Parameters Of Interest-resultssupporting
confidence: 77%
See 1 more Smart Citation
“…There were no significant differences between the exercise group and the ginger supplementation group, except in the measured weight of women, where the exercise group showed better results [29]. Results of the study conducted by Alghamdi confirmed a previous finding, where women treated with ginger capsules had lower values of BMI, insulin, and high and low-density lipoproteins [30].…”
Section: Parameters Of Interest-resultssupporting
confidence: 77%
“…Obesity induces mild-chronic inflammation in the adipose tissue which increases insulin resistance. Samera A., in his study, showed that ginger reduces serum levels of fasting glucose, glucose, and low-and high-density lipoproteins [30].…”
Section: The Effects Of Ginger and Cinnamon On Obesity And Overweightmentioning
confidence: 94%